Midwives' perceptions on using a fetoscope and Doppler for fetal heart rate assessments during labor: a qualitative study in rural Tanzania - Paschal Francis Mdoe; Hege Langli Ersdal; Estomih Mduma; Robert Moshiro; Hussein Kidanto; Columba Mbekenga (BMC, 2018)
Abstract Background The Doppler is thought to be more comfortable and effective compared to the fetoscope for assessing the fetal heart rate (FHR) during labor. However, in a rural Tanzanian hospital, midwives who had easy access to both devices mostly used fetoscope. This study explored midwives' perception of factors influencing their preference for using either a Pinard fetoscope or a FreePlay wind-up Doppler for intermittent FHR monitoring. Methods Midwives who had worked for at least 6 months in the labor ward were recruited. Focus group discussion (FGD) was used to collect data. Five FGDs were conducted between December 2015 and February 2016. Qualitative content analysis was employed using NVivo 11.0. Results Three main themes emerged as factors perceived by midwives as influencing their preference; 1) Sufficient training and experience with using a device; Midwives had been using fetoscopes since their midwifery training, and they had vast experience using it. The Doppler was recently introduced in the maternity ward, and midwives had insufficient training in how to use it. 2) Ability of the device to produce reliable measurements; Using a fetoscope, one must listen for the heartbeat, count using a watch, and calculate, the Doppler provides both a display and sound of the FHR. Fetoscope measurements are prone to human errors, and Doppler measurements are prone to instrumental errors. 3) Convenience of use and comfort of a device; Fetoscopes do not need charging, and while it is possible to "personalize/hide" the measurements, and may be painful for mothers. Dopplers need charging and do not cause pain, but provide limited privacy. Conclusion Midwives' preferences of FHR monitoring devices are influenced by the level of device training, experience with using a device, reliable measurements, and convenience and comfort during use. Fetoscopes and Dopplers should be equally available during midwifery training and in clinical practice.